Forgery of Travel Documents - Criminalistics Aspect - Bojanić, Nebojša (Kriminalističke teme, 2002)
This article is continuation of this theme previous volume, which says about a problem of the forgery travel documents. The law aspect was represented in previous article, but, now in this article is represented criminalistics aspects of this problem. It is presented one statistics data analysis, and it made data processing of colecting informations of this subject mater. Colected informations are opening posibHyties future investigations in this field. The results of these investigations have purpose if they can be used well for analytics data processing and conclusions, for using necessary increase activitesfor securing border lines and clearing possible oversight.